2021
DOI: 10.1111/1759-7714.14235
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA circ_0008037 facilitates tumor growth and the Warburg effect via upregulating NUCKS1 by binding to miR‐433‐3p in non‐small cell lung cancer

Abstract: Background: Circular RNAs (circRNAs) participate in the genesis and progression of tumors, including non-small cell lung cancer (NSCLC). At present, the role and regulatory mechanisms of circRNAs in NSCLC have not been fully elucidated. The aim of this study was to explore the role and regulatory mechanism of circRNA hsa_circ_0008037 (circ_0008037) in NSCLC. Methods: Expression of circ_0008037 in NSCLC tissues and cells was detected by quantitative real-time polymerase chain reaction (RT-qPCR). Loss-of-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In NSCLC, Zhao et al noticed that NUCKS1 can promote NSCLC proliferation, invasion and migration through upregulating CDK1 expression [ 43 ]. Yu et al demonstrated that circRNA circ_0008037 promotes tumor growth and the Warburg effect by upregulating NUCKS1 through binding to miR-433-3p in NSCLC [ 44 ]. Our investigation demonstrates that circATP9A associates with HuR, thereby enhancing its expression, which in turn results in increased regulation of NUCKS1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, Zhao et al noticed that NUCKS1 can promote NSCLC proliferation, invasion and migration through upregulating CDK1 expression [ 43 ]. Yu et al demonstrated that circRNA circ_0008037 promotes tumor growth and the Warburg effect by upregulating NUCKS1 through binding to miR-433-3p in NSCLC [ 44 ]. Our investigation demonstrates that circATP9A associates with HuR, thereby enhancing its expression, which in turn results in increased regulation of NUCKS1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA has been identified to be a potential target for many cancers, including NSCLC. 19,20 Here, we investigated the role of circCCDC134, a highly expressed circRNA, in the NSCLC malignant phenotype. Our results revealed that circCCDC134 knockdown inhibited NSCLC cell growth, metastasis and glycolysis, and could effectively reduce NSCLC tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to continue to reveal more effective molecular targets to provide ideas for targeted therapy of NSCLC. CircRNA has been identified to be a potential target for many cancers, including NSCLC 19,20 . Here, we investigated the role of circCCDC134, a highly expressed circRNA, in the NSCLC malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%